Editorial preface - Eva Mayerhöffer (Journalistica, 2022)
Journalistica's editor-in-chief, Eva Mayerhöffer, presents the 2022 issue and introduces the new, more continuous publication format, where incoming contributions are published online first and published in a single issue at the end of each year.